2015
DOI: 10.4067/s0717-95022015000200058
|View full text |Cite
|
Sign up to set email alerts
|

Estudio Morfológico de la Retina de Salmones (Salmo salar)

Abstract: RESUMEN: La retina de peces teleósteos como pez cebra, se ha transformado en un importante modelo para el estudio de la plasticidad neuronal y la neurogénesis. Se ha demostrado además que la retina experimenta cambios ontogenéticos para adaptarse a distintos medios ambientes durante su vida. Este estudio tiene como objetivo describir el desarrollo ontogenético de la retina del alevín de salmón desde la eclosión hasta la fase de juvenil. Se trabajó con 30 salmones divididos en tres grupos de 10. Grupo I: recién… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Regarding spinal column deformation, the findings of the current work are consistent with those of Castro et al (2011). It has also been reported that continuous hypoxia, induced by culture density, affects skeletal development by altering the expression of genes related to bone metabolism in Atlantic salmon (Pelloń et al, 2015). Our results point in the same direction as the findings reported by Shang and Wu (2004), who point out that aquatic hypoxia in embryos generates congenital malformations.…”
Section: Association Between Exposure To Hypoxia and The Presentation...supporting
confidence: 91%
“…Regarding spinal column deformation, the findings of the current work are consistent with those of Castro et al (2011). It has also been reported that continuous hypoxia, induced by culture density, affects skeletal development by altering the expression of genes related to bone metabolism in Atlantic salmon (Pelloń et al, 2015). Our results point in the same direction as the findings reported by Shang and Wu (2004), who point out that aquatic hypoxia in embryos generates congenital malformations.…”
Section: Association Between Exposure To Hypoxia and The Presentation...supporting
confidence: 91%